2020
DOI: 10.1136/bcr-2020-235581
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of vertical transmission of SARS-CoV-2 after induction of labour in an immune-suppressed SARS-CoV-2-positive patient

Abstract: We present a case of a 38+1 weeks pregnant patient (G1P0) with a proven COVID-19 infection, who was planned for induction of labour because of pre-existent hypertension, systemic lupus erythematosus, respiratory problem of coughing and mild dyspnoea without fever during the COVID-19 pandemic in March 2020. To estimate the risk of vertical transmission of Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) during labour and delivery, we collected oropharyngeal, vaginal, urinary, placental and neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
1
15
0
8
Order By: Relevance
“…# cases only included if specified as spontaneous preterm birth. Maternal Medical Condition Number of women Percentage of total cases examined (%) References Gestational diabetes 7 2 [ 19 , 20 , 28 , 33 , 60 ] Pre-existing diabetes 2 0.6 [ 21 , 57 ] Hypertensive disorders of pregnancy 18 5 [ 18 , 19 , 21 , 24 , 25 , 28 , 31 , 53 , 60 ] Obstetric cholestasis 1 0.3 [ 28 ] Acute cholecystitis 1 0.3 [ 52 ] Cardiovascular disease 1 0.3 [ 21 ] Metabolic acidosis 1 0.3 [ 51 ] Respiratory failure 2 0.6 [ 24 , 25 ] Preterm prelabour rupture of membrane …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…# cases only included if specified as spontaneous preterm birth. Maternal Medical Condition Number of women Percentage of total cases examined (%) References Gestational diabetes 7 2 [ 19 , 20 , 28 , 33 , 60 ] Pre-existing diabetes 2 0.6 [ 21 , 57 ] Hypertensive disorders of pregnancy 18 5 [ 18 , 19 , 21 , 24 , 25 , 28 , 31 , 53 , 60 ] Obstetric cholestasis 1 0.3 [ 28 ] Acute cholecystitis 1 0.3 [ 52 ] Cardiovascular disease 1 0.3 [ 21 ] Metabolic acidosis 1 0.3 [ 51 ] Respiratory failure 2 0.6 [ 24 , 25 ] Preterm prelabour rupture of membrane …”
Section: Resultsmentioning
confidence: 99%
“…Corticosteroids were administered to a total of 43 women (in 15 reports) [ 16 , 17 , 19 , 20 , 32 , 33 , [37] , [38] , [39] , 41 , 45 , 46 , 49 , 51 , 53 ]. Four studies reported that the corticosteroids were primarily given for prophylaxis against fetal lung disease [ 32 , 38 , 49 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis was based on 745 COVID infected cases and 219 controls. A total of 34 case reports [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ] yielding 45 cases were also included in the descriptive data analysis. Majority of the studies (12/34) were from China, 7 from the USA [ 62 , 67 , 68 , 70 , 76 , 85 , 87 ], 2 from Iran [ 63 , 80 ], 2 from Netherlands [ 82 , 83 ], 1 from Peru [ 75 ], 1 from Italy 1 [ 84 ], 1 from Sweden [ 64 ], 1 from Spain [ 73 ], 1 from Korea [ 55 ], 1 from Turkey [ 56 ], 1 from UK [ 78 ], 1 from Australia [ 88 ], 1 from Canada [ 79 ], 1 from Jordon [ 86 ], and 1 from India [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Case reports from Korea [ 55 ], India [ 72 ], Netherlands [ 82 , 83 ], Australia [ 88 ], Italy [ 84 ], Ireland [ 82 ], and Turkey [ 56 ] did not show any adverse pregnancy outcomes. All of these cases were detected after the gestation age of 35 weeks except for one case in a study [ 82 ].…”
Section: Discussionmentioning
confidence: 99%